PERGAULAN MENURUT AMSAL 17:17 SEBAGAI MAKHLUK SOSIAL DALAM KEBERSAMAAN - Keli Kiawati; Agus Prayitno M. Th (Sekolah Tinggi Teologi Imauel Pacet, 2021)
Association according to Proverbs 17:17 A friend loves at all times, and becomes a brother in adversity as a social being in togetherness. Association can be used to do good things, not bad things, everyone is a social being who cannot live alone, therefore, whether he wants to or not, he must continue to socialize. The purpose of good association is to add friends, respect each other, find information, because they are social beings, grow together, help each other, and so on. While the purpose of bad association is to take advantage of all means, bring down others, seek pleasure, debauchery, violate applicable rules. Good association will help to have friends. The benefits of having friends can help each other, relieve loneliness, there are those who give advice, remind each other, care, build each other up, trigger positive behavior and others. The strategies that are usually used in socializing to be friendly are having a sincere heart, being light-hearted, willing to listen to others, understanding needs, willing to start a conversation, not being offended quickly, understanding limits in acting, joking, and respecting the privacy of others. And instill a sense of caring, tolerance, and high social attitudes. Association can be used to apply love to others, love needs to be proven not just said. Through the association can form individual personalities, often encounter individuals who are influenced by their association. Therefore, this association is important to pay attention to, because if the association is damaged it will have a bad impact. togetherness can be built in social life by means of mutual cooperation, holding joint activities and so on to support intimacy.